ATRT-08. TARGETING THE TP53-MDM2 ENHANCES RADIATION SENSITIVITY IN ATRT. (1st June 2021) - Alimova, Irina; Danis, Etienne; Wang, Dong; Pierce, Angela; Serkova, Natalie; Venkataraman, Sujatha; Vibahakar, Rajeev
Abstract: Atypical Teratoid Rhabdoid Tumor is a highly aggressive pediatric brain tumor. Despite radiation, aggressive chemotherapy and autologous stem cell rescue, the children usually have poor survival. A functional genomic screen identified the TP53-MDM2 axis as a therapeutic vulnerability in ATRT. Gene expression demonstrates that all ATRT sub-groups have high level of MDM2 a negative regulator of p53. We demonstrate that MDM2 inhibition by shRNA or with small-molecule drugs, Nutlin3 and Idasanutlin resulted in decreased ATRT cell growth, inhibition of clonogenic potential and induction of apoptosis in vitro and in vivo. MRI imaging of intracranial tumors shows that Apparent Diffusion Coefficient (ADC), a good marker for successful treatment, significantly increased with Idasanutlin treatment showing tumor necrosis. Moreover, Idasanutlin significantly decreased growth of intracranial orthotopic ATRT brain tumors as evaluated by T2 MRI imaging and prolonged survival compared to control animals. Further idasanutlin potentiated radiation induced DNA damage and increased sensitivity to radiaton of ATRT cells. These findings highlight the TP53-MDM2 axis as a rational therapeutic target in ATRT.